Meta-Analysis on the Chinese Herbal Formula Xiaoer-Feike Granules as a Complementary Therapy for Children With Acute Lower Respiratory Infections - Qiang You; Qiang You; Lan Li; Dan Li; Dan Yang; Lin Chen; Hong-ping Chen; You-ping Liu (Frontiers Media S.A., 2020)
BackgroundOver the past five years the Chinese herbal formula (CHF) medicine, Xiaoer-Feike granules (XFG), has become a widely used adjuvant therapy for acute lower respiratory infections (ALRI). Considering the rapid popularization and application of XFG, and the lack of systematic evidence evaluating its effectiveness and safety in treating ALRI, it is necessary to conduct a meta-analysis to determine its benefits for patients.MethodsThis study systematically identified randomized controlled trials (RCTs) of XFG treatments for ALRI through July 2019 using four English-databases (PubMed, Cochrane Library, Ovid, and Web of Science) and four Chinese-databases (Sino-med database, China National Knowledge Infrastructure (CNKI), VIP database, and the WANFANG database). We then performed a quality assessment and data analysis with Review Manager 5.3.5 and Stata 15.1.ResultsTwenty-one RCTs involving 3425 patients were randomly divided into an XFG group and a conventional medicine (CM) group. The results showed that the clinical efficacy rate (CER) of the XFG group was significantly higher than that of the CM group (RR=1.17, 95% CI =1.13-1.22, P< 0.00001). In comparison with the CM group, the XFG group had strikingly shortened: resolution time of cough (RTC) (MD = -1.92; 95% CI =-2.33, -1.51, P<0.00001); resolution time of rale (RTR) (MD = -1.68; 95% CI =-2.27, -1.10, P<0.00001); resolution time of fever (RTF) (MD = -1.46; 95% CI =-1.92, -1.00, P<0.00001); resolution time of inflammatory lesions (RTIL) (MD = -2.43, 95% CI =-2.94, -1.93, P< 0.00001); and hospital stays (HS) (MD = -2.26, 95% CI =-3.03, -1.49, P< 0.00001). At the cellular and molecular level, the CD4, CD8, CD4/CD8, IL-6, TNF-α, and CRP levels were significantly improved when CM was complemented with XFG. In addition, no significant difference was observed between the XFG and CM groups in terms of the adverse events (AE) (RR =0.97, 95% CI= 0.61-1.54, P= 0.89).ConclusionsThe findings of this meta-analysis support the use of XFG in the treatment of ALRI. However, these results should be treated with caution due to the significant heterogeneity and publication bias of existing data. Further well-designed and high-quality RCTs are needed to interrogate the efficacy and safety of XFG.